Effect of CMP fiber grafting on strength properties of its paper - Iman Rashidi joibari (Regional Information Center for Science and Technology (RICeST), 2013)
Mechanical and chemi-mechanical pulps such as CMP, due to the weaker strength properties, have found limited application in the production of high quality papers as compared with chemical pulps. Therefore, appropriate modification of such fibers could be used to overcome such deficiencies. This study investigated the effect of cationic pretreatment of the CMP fibers to improve the potential of the fibers in paper production. First, fibers were treated by 20% sodium hydroxide, and then the fiber surface was cationized by grafting with one of the dosages of 5, 10 and 15% EPTMAC, based on fiber oven dry weights. The cationized fibers were mixed with 100, 20 and 40 % non-cationized fibers and the mixture was used to make hand sheets. The tensile and burst indices of the hand sheets were measured. The highest tensile and burst indices were measured on hand sheets produced containing either 20 or 40% fibers grafted with 10% cationic agent.